MAKNA TERSELUBUNG PIDATO KENEGARAAN PRESIDEN SUSILO BAMBANG YUDHOYONO: ANALISIS WACANA KRITIS - Ambar Andayani (Universitas 17 Agustus 1945 Surabaya, 2009)
Abstract. The focus of this research is the semantic aspect in the form of various implied meaning of the text of the state address of President Susilo Bambang Yudhoyono during his reign of 2004-2008. In the perspective of critical discourse analysis, it can be shown five implied meanings as follows: to answer the demands of the public, garnering support from many circles, building optimism to the people, boost self-image in the public eye, and muffled criticism of the political opponent / rival. In his state address, it is discovered that SBY discredited his political rival groups impliedly.Â Key words: semantic, textual meanings, hidden meanings, critical discourse analysis